2018
DOI: 10.1111/jse.12464
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyletic Alyssum cuneifolium (Brassicaceae) revisited: Morphological and genome size differentiation of recently recognized allopatric taxa

Abstract: Alyssum cuneifolium has been recognized as a perennial alpine species growing in five isolated European mountain ranges: the Pyrenees, Western Alps, Apennines, Pirin Mts and Mt Smolikas. Recent molecular systematic studies revealed that the disjunct populations from distant mountains are not closely related and belong to five independent species: A. cacuminum (Spain, Pyrenees), A. cuneifolium (Italy, Apennines), A. flexicaule (France, Western Alps), A. pirinicum (Bulgaria, Pirin Mts), and A. spruneri (Greece, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Monoploid relative genome size (relative C x value) was calculated as the relative 2C DNA value divided by the number of chromosome sets x . Our recent studies of Brassicaceae genera have shown that the correlation between absolute and relative DNA content values is almost perfect (Marhold et al., ) and that silica gel‐dried leaf material can be used to identify genuine differences in relative genome size (Šlenker et al., ; Španiel et al., , ). Differences in monoploid relative genome size between the genetic groups of A. repens were tested with Kruskal‐Wallis tests followed by Mann‐Whitney pairwise comparisons with Bonferroni correction of P‐values using PAST 3 (Hammer et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monoploid relative genome size (relative C x value) was calculated as the relative 2C DNA value divided by the number of chromosome sets x . Our recent studies of Brassicaceae genera have shown that the correlation between absolute and relative DNA content values is almost perfect (Marhold et al., ) and that silica gel‐dried leaf material can be used to identify genuine differences in relative genome size (Šlenker et al., ; Španiel et al., , ). Differences in monoploid relative genome size between the genetic groups of A. repens were tested with Kruskal‐Wallis tests followed by Mann‐Whitney pairwise comparisons with Bonferroni correction of P‐values using PAST 3 (Hammer et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The Alyssum montanum – A. repens group (Brassicaceae) is a polyploid species complex that displays high species and genetic diversity in the Mediterranean and adjacent regions, as well as in mountainous areas (Ball and Dudley, ; Jalas et al., ; Španiel et al., 2011b, , b; Zozomová‐Lihová et al., 2014b). Most species show fairly restricted, allopatric distribution ranges, several are local endemics whereas only a few are more widespread, and even those show geographically structured genetic variation (Zozomová‐Lihová et al., 2014b; Španiel et al., 2017b, ). In fact, several mountain ranges in Europe (the Pyrenees, Alps, Apennines, Carpathians, and Dinarides) harbor at least one endemic taxon from this species complex (Španiel et al., 2011b, , 2017b, , ; Magauer et al., ; Zozomová‐Lihová et al., 2014b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar scenarios of independent colonization of alpine habitats by several distinct genetic lineages from foothill areas were recently inferred also in Arabidopsis arenosa (Kolář et al, 2017) and in the formerly broadly conceived species Alyssum cuneifolium (Španiel et al, 2019). In both these cases, the overall phenotypic similarity of alpine populations contrasting with their genetic heterogeneity has been caused by a similar (alpine) environment (Kolář et al, 2017;Monnahan et al, 2019;Španiel et al, 2019;Wos et al, 2019).…”
Section: Taxonomic Implicationsmentioning
confidence: 99%
“…Flow cytometry (FCM), which is a fast and effective tool to estimate GS, has been successfully applied to ploidy identification, cell cycle analysis, and species identification, including hybrids, rarely occurring cytotypes, and aneuploids (Francis et al., 2008; Hanusova et al., 2014; Vit et al., 2014; Zhang et al., 2019). It has been used successfully in plant genetic variation studies, genetic analyses, and breeding, as well as in studies of reproductive ecology, evolution, and plant system classification (Bilinski et al., 2018; Galbraith, 2004; Sharma et al, 2019; Spaniel et al., 2019). In the 1980s, Galbraith et al.…”
Section: Introductionmentioning
confidence: 99%